APLIKASI PENGELOLAAN SERVIS KOMPUTER DI DEWA KOMPUTER BERBASIS WEB : APLIKASI PENGELOLAAN SERVIS KOMPUTER DI DEWA KOMPUTER BERBASIS WEB - adi samsara adi samsara (LPPM Universitas Merdeka Madiun, 2023)
Dewa Computer is a computer service shop located in the Ngawi district. In addition to servicing computers, Dewa Computer also provides various needs for computer spare parts. However, at this point in the service operational process, the service has not implemented a technology and system at all. In addition, in the process of storing data and recording it is still conventional to use recorded data, this is often an obstacle and human error often occurs. Furthermore, this causes the development and efficiency of its operations to be slow and less than optimal. To be able to change and maximize the potential that exists, in this study a service data management information system was created. This information system is made web-based using the Waterfall method, while for testing the feasibility of the system using the Blackbox testing method. This system is expected to assist owners in service business operations and make it easier for owners and technicians to manage service data to make it more efficient and effective.